The handbag. Issue 2 (4th March 2022) - Rosenberg, Laura; Turunen, Linda Lisa Maria; Järvelä, Saara-Maija; Arnould, Eric
Abstract: The woman's handbag is an iconic consumer artefact layered with meaning. Ideologies, economics, culture, social statuses, and identities converge in this object. Superfluous but fetishized luxury, essential useful tool, communications device, fashion arbiter, all this and more. To shed light on this fascinating artefact and its journey to a contemporary marketplace icon, we first clarify how the iconicity of the handbag emerged and changed over time. Tracking historical turning points and changes in society offers a basis for understanding how the handbag displays its iconic value today. We conclude this marketplace essay by looking into the many ways that handbag consumption manifests in contemporary times, through consumers' everyday performances.